1992
DOI: 10.1111/j.1469-8137.1992.tb01097.x
|View full text |Cite
|
Sign up to set email alerts
|

The late Quaternary vegetational history of northwest Greece

Abstract: SUMMARYThe mountainous region of northwest Greece has often been cited as a possible area for the existence of temperate tree taxa during the last glacial. This series of papers examines the vegetational history and sedimentary history of two small basins in the Pindus mountain range of northwest Greece. The two basins are 18 km apart but at contrasting heights of 285 and 1800 m. The present paper describes results from the lowland basin of Gramousti lake. Techniques of pollen analysis, plant macrofossil analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
3

Year Published

1994
1994
2010
2010

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(13 citation statements)
references
References 29 publications
0
10
0
3
Order By: Relevance
“…The clear evidence of human activity in Stratum 6c, especially in the western part of the cave (trench XXI), would lend support to the interpretation that the wood charcoal in these levels is anthropogenic in origin. In Epirus, the pollen data from Ioannina (Bottema, 1974; Figure 15) and Lake Gramousti (Willis, 1992(Willis, , 1997; Figure 16) indicate that during the early post-glacial (ca. 11,000 yr B.P.)…”
Section: Environmental Reconstructionmentioning
confidence: 96%
See 1 more Smart Citation
“…The clear evidence of human activity in Stratum 6c, especially in the western part of the cave (trench XXI), would lend support to the interpretation that the wood charcoal in these levels is anthropogenic in origin. In Epirus, the pollen data from Ioannina (Bottema, 1974; Figure 15) and Lake Gramousti (Willis, 1992(Willis, , 1997; Figure 16) indicate that during the early post-glacial (ca. 11,000 yr B.P.)…”
Section: Environmental Reconstructionmentioning
confidence: 96%
“…oak and pine predominate in the sparse arboreal pollen, with maple and juniper also present, as at Konispol (Figure 15). For the period from 13,000 to 10,000 yr B.P., pollen data from Lake Gramousti at an elevation of 400 m asl (Figure 1) shows that trees were still sparse and deciduous oak and juniper would have formed an open forest or steppe-forest (Figure 16) (Willis, 1997(Willis, , 1992. Species such as almond, plane tree, buckthorn, and pistachio are barely or not at all represented in these Late Pleistocene spectra.…”
Section: Environmental Reconstructionmentioning
confidence: 97%
“…Gramousti lake basin at a height of 285 m a.s.l. (Figure 2) is thought to be a feature of the karstic landscape such as a doline (Willis 1992a). It is located within the wider environs of the Doliana basin although it is a hydrologically closed basin.…”
Section: Site Informationmentioning
confidence: 98%
“…Dating of the core by six AMS dates (Hedges et al 1990, Willis 1992a) revealed a sedimentary record spanning the last 14,000 years. Following a detailed study of the pollen and plant macrofossil material contained within the sediment (Willis 1992a), a pollen percentage diagram plotted against age was constructed and is presented in Figure 3.…”
Section: Vegetational Development Of the Lowland Regionmentioning
confidence: 99%
See 1 more Smart Citation